2011
DOI: 10.1002/jcla.20430
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of 14 human serum protein assays on the Roche cobas® c 501

Abstract: Many laboratories rely on dedicated nephelometers and turbidimeters for the measurement of serum proteins. There are, however, a number of chemistry analyzers that offer open channel configurations for end-user applications. We developed and validated 14 human serum protein assays (α(1)-antitrypsin, α(2)-macroglobulin, albumin, apolipoproteins AI and B, complement components 3 and 4, haptoglobin, immunoglobulins A, G, and M, orosomucoid, transferrin, and transthyretin) on the Roche cobas(®) c 501. We obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…AAT (g/litre) and C-reactive protein (CRP, mg/litre) concentrations were determined by latex-enhanced immunoturbidimetric assay (COBAS Integra analyzer, Roche Diagnostics, Indianapolis, Indiana, USA), a robust assay with principles that are perfectly comparable to those of nephelometry 12. The interassay coefficient of variation (CV) was 3.6–4.6%; lower detection thresholds for the AAT and CRP assays were 0.21 g/litre and 1 mg/litre, respectively, and reference values were 0.9–2.0 g/litre and <8 mg/litre, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…AAT (g/litre) and C-reactive protein (CRP, mg/litre) concentrations were determined by latex-enhanced immunoturbidimetric assay (COBAS Integra analyzer, Roche Diagnostics, Indianapolis, Indiana, USA), a robust assay with principles that are perfectly comparable to those of nephelometry 12. The interassay coefficient of variation (CV) was 3.6–4.6%; lower detection thresholds for the AAT and CRP assays were 0.21 g/litre and 1 mg/litre, respectively, and reference values were 0.9–2.0 g/litre and <8 mg/litre, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, the measurement of AAT levels in blood is mostly performed by nephelometry or, less commonly, a comparable latex-enhanced immunoturbidimetric assay (table 1) [26].…”
Section: Laboratory Diagnosis and Hierarchy Of Testingmentioning
confidence: 99%
“…Denham et al [29] demonstrated that by their performance characteristics, the Architect ci8200 immunoturbidimetric specific protein assays are suitable for routine use, and correlate well with representative immunonephelometric assays on the Beckman Immage analyzer. In a study of Ledue et al [25], in which they evaluated the method performance characteristics of 14 serum protein analytes (alfa 1-antitrypsin, alfa 2-macroglobulin, albumin, apolipoproteins AI and B, C3, C4, haptoglobin, IgA, IgG, IgM, orosomucoid, transferrin and transthyretin) in Roche Cobas C501, they found an excellent correlation between immunonephelometric and immunoturbidimetric assays.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoturbidimetric assays have been improved considerably over time. These improvements include advances in antibody purification techniques, enhancements in instrument design and function and production of new reference materials based on global standardization initiatives [22][23][24][25][26]. Additional practical advantages of immunoturbidimetric protein assays include random access analysis instead of batch testing, relatively rapid turn around time, high volume testing capability, cost reduction through consolidation of testing on a single platform, elimination of stand alone specialized analyzers, and time and effort required to maintain them [21].…”
Section: Introductionmentioning
confidence: 99%